In vivo effect of bevacizumab-loaded albumin nanoparticles in the treatment of corneal neovascularization. (August 2019) - Luis de Redín, Inés; Boiero, Carolina; Recalde, Sergio; Agüeros, Maite; Allemandi, Daniel; Llabot, Juan M.; García-Layana, Alfredo; Irache, Juan M.
Abstract: Corneal neovascularization (CNV) is associated with different ocular pathologies, including infectious keratitis, trachoma or corneal trauma. Pharmacological treatments based on the topical application of anti-VEGF therapies have been shown to be effective in the treatment and prevention of CNV. The aim of this work was to evaluate the effect of bevacizumab-loaded albumin nanoparticles in a rat model of CNV. Bevacizumab-loaded nanoparticles, either "naked" (B-NP) or coated with PEG 35, 000 (B-NP-PEG), were administered once a day in the eyes of animals (10 μL, 4 mg/mL every 24 h) during 7 days. Bevacizumab and dexamethasone were employed as controls and administered at the same dose every 12 h. At the end of the study, the area of the eye affected by neovascularization was about 2-times lower for animals treated with B-NP than with free bevacizumab. In the study, dexamethasone did not demonstrate an inhibitory effect on CNV at the employed dose. All of these results were confirmed by histopathological analysis, which clearly showed that eyes treated with nanoparticles displayed lower levels of fibrosis, inflammation and edema. In summary, the encapsulation of bevacizumab in human serum albumin nanoparticles improved its efficacy in an animal model of CNV. Graphical abstract: Image 1 Highlights: Bare and pegylated nanoparticles were prepared for the encapsulation of bevacizumab. Nanoencapsulated bevazicumab were evaluated in a corneal neovascularization model. Bare nanoparticles displayed a higher antiangiogenic effect than free bevacizumab. Pegylation did not improve the angiogenic effect observed with bare nanoparticles.